Circular RNA in colorectal cancer. Issue 8 (9th March 2021) - Li, Anthony; Wang, Wei Cen; McAlister, Vivian; Zhou, Qinfeng; Zheng, Xiufen
Abstract: Circular RNA (circRNA) is a highly abundant type of single‐stranded non‐coding RNA. Novel research has discovered many roles of circRNA in colorectal cancer (CRC) including proliferation, metastasis and apoptosis. Furthermore, circRNAs also play a role in the development of drug resistance and have unique associations with tumour size, staging and overall survival in CRC that lend circRNAs the potential to serve as diagnostic and prognostic biomarkers. Among cancers worldwide, CRC ranks second in mortality and third in incidence. In order to have a better understanding of the influence of circRNA on CRC development and progression, this review summarizes the role of specific circRNAs in CRC and evaluates their potential value as therapeutic targets and biomarkers for CRC. We aim to provide insight in the development of therapy and clinical decision‐making.